2023
DOI: 10.1049/hve2.12317
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic ageing research of cross‐linked polyethylene cable insulation based on temporal‐spatial dimension under combined electro‐thermal effect

Abstract: Dynamic ageing process of cross‐linked polyethylene (XLPE) cable insulation under combined electro‐thermal effect is investigated by the construction of theoretical analysis model and the practice of operation‐simulated ageing test. Firstly, theoretical analysis model is constructed from time and spatial dimensions. From the time dimension, in the light of the impeding trend of internal stress to external stress, the XLPE ageing process of Steady state ‐Transition state ‐Steady state (STS) is proposed to illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To quantitatively analyze the migration of low polar molecules on the perfor of the cable insulation, the aromatic ring index (ARI), vinyl index (VI), and pheno (PI) are introduced. The definition of these three indexes is as follows [14]: In Figure 5a, it is observed that prominent absorption peaks at 1596, 1650, and 3370 cm −1 exist in the inner insulating layers of S7. For S7-1 and S7-2, minor changes in these peaks in the range of 1700 to 1800 cm −1 , compared to S7, indicate that thermaloxidative aging hardly happens during the aging test.…”
Section: Results Of Ftir Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantitatively analyze the migration of low polar molecules on the perfor of the cable insulation, the aromatic ring index (ARI), vinyl index (VI), and pheno (PI) are introduced. The definition of these three indexes is as follows [14]: In Figure 5a, it is observed that prominent absorption peaks at 1596, 1650, and 3370 cm −1 exist in the inner insulating layers of S7. For S7-1 and S7-2, minor changes in these peaks in the range of 1700 to 1800 cm −1 , compared to S7, indicate that thermaloxidative aging hardly happens during the aging test.…”
Section: Results Of Ftir Measurementmentioning
confidence: 99%
“…To quantitatively analyze the migration of low polar molecules on the performances of the cable insulation, the aromatic ring index (ARI), vinyl index (VI), and phenol index (PI) are introduced. The definition of these three indexes is as follows [14]:…”
Section: Results Of Ftir Measurementmentioning
confidence: 99%
See 1 more Smart Citation